PROFESSOR ANASTASII ZAIKEVYCH (1842–1931): POLTAVA PORTRAIT ON THE BACKGROUND OF TIME - Samorodov, V.; Pospelov, S. (Scientific Progress & Innovations, 2022)
The purpose of the review was to summarize information and introduce into scientific circulation littleknown facts of the biography of A. Ye. Zaikevych. It is stated that the creative destiny of the classic of Ukrainian agrarian science is closely connected with his small homeland – Poltava region, the synergy of these relations, their multifaceted component, the creative content of which remains relevant, is stated. It is established that it was in Poltava region that the preconditions and main factors of forming the civic and national worldview of the scientist were created. He proved to be a propagandist of Taras Shevchenko's life and work. His creative local lore relations with such leading figures of Ukrainian culture as Mykola Lysenko and Klyment Kvitka were fruitful. All this contributed to the fact that A. Ye. Zaikevych became one of the most outstanding ethnographers of his time, especially in the field of ceramics. The printed works of the scientist in this area were included in the golden fund of national folk art. A. Ye. Zaikevych made efforts to form important centers of education and culture of the region – the modern Lubny Forest College NULES and Myrhorod Art and Industrial College named after M. V. Gogol of PNTU named after Yuri Kondratyuk. During the period from 1855 to 1929 he was one of the initiators of the Poltava, Lokhvytsia, Mlyniv research fields, Solonytsia research station and Lubny research station on medicinal plant culture. The researcher's contribution to the development of sheep breeding, beekeeping, selection and seed production is specified. The educational and consultative activity of A. Ye. Zaikevych as a part of professional and special meetings, congresses and exhibitions of the Poltava provincial zemstvo, and also the Poltava society of agriculture and its branches is found out. The importance of the scientist's creative work for the development of socioeconomic conditions of the region and its impact on its modern progress is argued.